2017
DOI: 10.1111/jcmm.13058
|View full text |Cite
|
Sign up to set email alerts
|

A functional variant in ST2 gene is associated with risk of hypertension via interfering MiR‐202‐3p

Abstract: Recent studies have suggested that interleukin 1 receptor‐like 1 (ST2) plays a critical role in pathogenesis of several cardiovascular disease conditions. In this study, we examined association of 13 single nucleotide polymorphisms (SNPs) of ST2 gene with essential hypertension (EH) risk in 1151 patients with EH and 1135 controls. Our study showed that variants rs11685424, rs12999364 and rs3821204 are highly associated with an increase in risk of EH, while rs6543116 is associated with a decrease risk of EH. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
(53 reference statements)
2
19
0
Order By: Relevance
“…Previous study showed that the rs3821204 disrupted a miR‐202‐3p seeding site, resulted in an allelic difference of sST2 mRNA stability and expression, and finally modified the susceptibility of hypertension . In this study, we cotransfected rs3821204 G or C plasmid with miR‐202‐3p mimics (50 μmol/L) or negative control into HEK293 cells and confirmed the alteration of miR‐202‐3p binding site and a significantly decreased luciferase activity of rs3821204‐G but not rs3821204‐C (Figure A,B).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Previous study showed that the rs3821204 disrupted a miR‐202‐3p seeding site, resulted in an allelic difference of sST2 mRNA stability and expression, and finally modified the susceptibility of hypertension . In this study, we cotransfected rs3821204 G or C plasmid with miR‐202‐3p mimics (50 μmol/L) or negative control into HEK293 cells and confirmed the alteration of miR‐202‐3p binding site and a significantly decreased luciferase activity of rs3821204‐G but not rs3821204‐C (Figure A,B).…”
Section: Resultssupporting
confidence: 72%
“…The insert sequences (rs7025417T and rs7025417C) were verified by Sanger sequencing. Plasmid containing the ST2 rs3821204 G or rs3821204 C was constructed as described previously . Briefly, The 3′‐UTR fragment of ST2 was amplified using the following primers: 5′‐GTCTCTAGAATCCCCCACTCCCTCC‐3′ (forward) and 5′‐CAGTCTAGAATCTGTGTTCCTGCCC‐3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ct refers to the number of amplification cycles when the real-time fluorescence intensity reached the set threshold whereby the amplification procedure was in the logarithmic growth phase. The measurement was repeated 3 times [24][25][26].…”
Section: Rna Isolation and Quantitationmentioning
confidence: 99%
“…A previous study of our lab demonstrated the critical role of miR-202-3p in essential hypertension. 6) Numerous studies also indicated that miR-202-3p functions as a tumor suppressor in the carcinogenesis of multiple solid tumors including bladder, breast, colorectal, gastric, and pancreatic cancers. [7][8][9][10] A gene-annotation enrichment analysis for potential targets of miR-202-3p suggested that it might be implicated in cardiovascular and metabolic diseases.…”
mentioning
confidence: 99%